An Empirical Analysis of Forest Transition in Uttarakhand, India through Environmental Kuznets Curve Approach - Ashraf, Jawaid; Bhojvaid, Padam Prakash; Pandey, Rajiv; Jong, Wil De (Indian Forester, 2018)
India experienced forest transition (FT) as the forest cover from 75.8 million ha in 1950 reduced to 62.9 million ha in 1970 and with reforestation, increased to 69.2 million ha in 2010. In India, Various drivers such as economic sector, demographic sector, government policies directly or indirectly influencing forest cover change at national level. Present paper provide an empirical evidence of forest cover change at sub-national level with focus to Uttarakhand state based on the environmental Kuznets curve (EKC) model. The secondary data for the period 1990 to 2014 was used for the model development between forest cover and its contextual drivers. The results are in accordance with the hypothesis of EKC model for contextual drivers i.e. income and livestock population. These two drivers explains 93% variability of forest cover based on quadratic model for the state and concludes that the forest cover change be effectively accounted and managed based on the changes in the state economic condition and socioeconomic profiles of the state. Thus, policy planners should orient their planning of forest conservation in holistic manner by integrating the state economic and socioeconomic profile.